The Latest Developments and Future Trends of Australian Food Industry under the Concept of Sustainability - TAN Hong-zhuo; FANG Zhong-xiang; YI Cui-ping (Liang you shipin ke-ji)
In order to understand the latest situation and future trends of the Australia food industry under the concept of sustainability development, we have overviewed the circumstances of food safety and waste in Australia, the impact of food industry on greenhouse gas emission and the environment, which promote sustainable development. The strategic approach focuses on comprehensive ways across the entire supply chain from farm to table, such as exploiting alternative protein food resources, learning adaptability from Aboriginal people, developing the fairer and more sustainable value chain, transitioning from a liner food chain to food web, upgrading the usage of food waste, etc. It also plays a role of food processing to improve food safety and sustainability, absorbing digital transformation technology, 5G, Artificial Intelligence, alternative protein and food safety technology innovation. It vigorously develops plant-based foods, space foods and marine foods, etc. Under the concept of sustainable development, the Australian government place great importance on biodiversity protection and supervision. The associations and institutes related to the food industry also make positive contributions on research investment and anti-food-waste efforts. Food enterprises embrace sustainable development as a mind set and operation approach, considering the planet as a key stakeholder, which demonstrates a society responsibility. Australia places more emphasis on the impact of the food industry on the planet's environment, leading to the popularity of plant-based foods. It will be a better future for the sustainable development of food industry in Australia through the joint efforts of stakeholders, which offers certain information references for food sector peers in China.